2019
DOI: 10.1089/hum.2018.192
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Gene Therapy in a Novel Mouse Model of HumanMFRP-Associated Retinopathy

Abstract: Patients harboring homozygous c.498_499insC mutations in MFRP demonstrate hyperopia, microphthalmia, retinitis pigmentosa, retinal pigment epithelial atrophy, variable degrees of foveal edema, and optic disc drusen. The disease phenotype is variable, however, with some patients maintaining good central vision and cone function till late in the disease. A knock-in mouse model with the c.498_499insC mutation in Mfrp (Mfrp KI/KI) was developed to understand the effects of these mutations in the retina. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…2 of 13 show disease characteristics similar to those found in Mfrp mouse models [12,13,[17][18][19]. Mutations in Adipor1 also result in fundus spots and PR cell death [17].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…2 of 13 show disease characteristics similar to those found in Mfrp mouse models [12,13,[17][18][19]. Mutations in Adipor1 also result in fundus spots and PR cell death [17].…”
Section: Introductionmentioning
confidence: 66%
“…Disruptions in MFRP are known to cause a spectrum of human ocular diseases, including hyperopia [4], nanophthalmos [5,6], posterior microphthalmos [7], retinitis pigmentosa [8], foveoschisis [9,10], and optic disc drusen [11]. Likewise, mouse models with mutations in Mfrp, including rd6 (4 bp deletion) [2], rdx (174delG mutation) [12], and a c.498_499insC knock-in [13], show phenotypic similarities to the human diseases such as hyperopia, reduced axial length, retinal degeneration, RPE atrophy, and decreased electrophysiological response. The Mfrp mouse models also show the presence of uniformly sized and evenly distributed white spots across the fundus, similar to the white flecks observed in the patients with MFRP mutations [14,15] and in the human flecked retinal disorder retinitis punctata albescens [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…When mutations in MFRP were first identified in humans [497], mice were thought to be a poor model because unlike humans [498], mice were previously reported to develop PR degeneration [499], and the microphthalmia and hyperopia found in human patients had not been reported in homozygous Mfrp rd6 mice. In subsequent years, numerous human patients have been identified that do show a degenerative phenotype [500] and hyperopia was detected both in a mouse model carrying a human MFRP c.498_499insC allele [501] and the original Mfrp rd6 mouse (our unpublished observations). An important family of deaf-blindness diseases, Usher syndrome, was also thought to be poorly recapitulated in mice, because early models like the shaker-1 mouse had only the characteristic hearing loss, but no retinal degeneration [502].…”
Section: Relationship To Human Disease Genesmentioning
confidence: 79%
“…Finally, a definite genetic diagnosis opens up opportunities for gene-based therapies in MFRP-associated retinal disease. Indeed, studies in two mouse models have demonstrated that MFRP-retinopathy is a potential target for gene-based therapy: Mfrp rd6 /Mfrp rd6 described by Dinculescu et al 53 and Mfrp KI/KI described by Chekuri et al 54 . Left panel: color fundus.…”
Section: Discussionmentioning
confidence: 99%